How do you factor x^3= -3x^2-2x?

1 Answer
Oct 13, 2015

x * (x + 1) * (x + 2) = 0

Explanation:

x^3 = -3x^2 - 2x

iff x * (x^2 + 3x + 2)=0

Now, choose two numbers, whose sum equals the the coefficient of x and whose product is the product of the coefficient of x^2 and the constant.

Here the coefficient of x is 3
The coefficient of x^2 is 1
and the constant is 2

So the numbers are 2 & 1

Thus the above expression can be written as

x * (x^2 + 2 x + x + 2)=0

that is x * {x * (x + 2) + 1 * (x + 2)}=0

which in turn can be written as

x * (x + 1) * (x + 2) = 0